Economic burden of sarcoidosis in a commercially-insured population in the United States. (3rd October 2017) - Rice, J. Bradford; White, Alan; Lopez, Andrea; Conway, Alexandra; Wagh, Aneesha; Nelson, Winnie W.; Philbin, Michael; Wan, George J.
Abstract: Background: Sarcoidosis is a multi-system inflammatory disorder characterized by the presence of non-caseating granulomas in involved organs. Patients with sarcoidosis have a reduced quality-of-life and are at an increased risk for several comorbidities. Little is known about the direct and indirect cost of sarcoidosis following the initial diagnosis. Aims: To provide an estimate of the healthcare resource utilization (HCRU) and costs borne by commercial payers for sarcoidosis patients in the US. Methods: Patients with a first diagnosis of sarcoidosis between January 1, 1998 and March 31, 2015 ("index date") were selected from a de-identified privately-insured administrative claims database. Sarcoidosis patients were required to have continuous health plan enrollment 12 months prior to and following their index dates. Propensity-score (1:1) matching of sarcoidosis patients with non-sarcoidosis controls was carried out based on a logistic regression of baseline characteristics. Burden of HCRU and work loss (disability days and medically-related absenteeism) were compared between the matched groups over the 12-month period following the index date ("outcome period"). Results: A total of 7, 119 sarcoidosis patients who met the selection criteria were matched with a control. Overall, commercial payers incurred 19, 714 in mean total annual healthcare costs per sarcoidosis patient. The principle cost drivers were outpatient visits (9, 050 2015 USD, 46%) and inpatient admissions (6, 398, 32%). Relative to controls, sarcoidosis patients had 5, 190 (36%) higher total healthcare costs (19, 714 vs 14, 524; p < 0.001). Sarcoidosis patients also had significantly more work loss days (15.9 vs 11.3; p < 0.001) and work loss costs (3, 288 vs 2, 527; p < 0.001) than matched controls. Sarcoidosis imposes an estimated total direct medical cost of 1.3–8.7 billion to commercial payers, and an indirect cost of 0.2–1.5 billion to commercial payers in work loss. Conclusions: Sarcoidosis imposes a significant economic burden to payers in the first year following diagnosis.